Miller Fisher syndrome associated with polycythemia vera: A rareclinical co-occurrence - balagopal, krishnan; S, Suneesh; Ann Joy, Mintu; Philip , Nikhil; Kuruvilla, Elizabeth; Pai, Anirudh (Indian Journal of Case Reports, 2026)
Miller Fisher syndrome (MFS) is a rare, acute immune-mediated neuropathy characterized by ophthalmoplegia, ataxia, and areflexia. Polycythemia vera (PV) is a chronic myeloproliferative neoplasm marked by autonomous erythroid overproduction and elevated thromboembolic risk. The clinical co-occurrence of these two distinct conditions is exceptionally rare. We report a case of a 42-year-old male presenting with a 3-day history of walking unsteadiness, bilateral eyelid drooping, and blurred vision following a low-grade fever. Diagnosis of MFS was confirmed through cerebrospinal fluid analysis, showing albumin-cytological dissociation, and a strongly positive serum anti-GQ1b antibody titer. Concurrently, severe erythrocytosis led to a bone marrow diagnosis of PV, notably testing negative for the Janus activated kinase gene but positive for the additional sex combs like 1 mutation. Despite compounded hyperviscosity and thrombotic risks, the patient was successfully treated with standard intravenous immunoglobulin and therapeutic venesection, resulting in full neurological resolution.